The Effect of Preventive Exercises on the Development of some Abilities Affecting Prevention from Injuries in Young Boxers - Tawfeeq, Abbaas; Jalal, Kamal (Journal of Physical Education, 2019)
The researchers, being former boxers, noticed that boxers suffer from many arm injuries thus the researchers aimed at designing preventive exercises to prevent arm injuries in young boxers. The researchers used the experimental method on (16) young boxers of different weight class. A set of preventive exercises was designed based on abilities that affect preventing injuries including flexibility, strength endurance, and strength – speed. The data was collected and treated using proper statistical operations to come up with the conclusions.